Retinal Findings in Two Patients With Tumefactive Multiple Sclerosis. Issue 3 (September 2019) - Neuhouser, Adam; Sanders, Riley; Burks, John R.; Chacko, Joseph
Abstract : Abstract: Tumefactive multiple sclerosis (TMS) often presents a diagnostic challenge because it can mimic neoplastic, infectious, or ischemic disease. We describe 2 patients with TMS with retinal findings of venous sheathing and bone spicule pigmentation. Mechanisms for such findings are discussed.